Wudu’ workstation design for elderly and disabled people in Malaysia’s mosques - Siti Zawiah, Md Dawal; Wan Nor Liza, Mahadi; Marizan, Mubin; Dian Darina Indah, Daruis; Shahrol, Mohamaddan; Farah Atikah, Abdul Razak; Nurul Izzah, Abdul Wahab; Mohd Haziq, Mohd Abd Wahab; Nursyahirah, Adnan; Siti Afifa, Anuar; Raziff, Hamsan (Iranian Journal of Public Health, 2016)
Background: Ablution area is one of the facilities used by most Muslims in all categories. There are numbers of de-sign guidelines for praying facilities but lack on ablution area specification. Therefore, this study was conducted to design an ergonomic ablution area for the Muslim’s disabled and elderly based on their preferences and anthropomet-ric dimension. Methods: Kano questionnaires and user evaluation form, was used to investigate the preferences of elderly and disa-bled in ablution area to 20 respondents at Masjid Bulat, Petaling Jaya and Masjid Kampung Kerinchi,Pantai Dalam, Kuala Lumpur in 2015. Anthropometric dimension of elderly and disabled people was measured. Besides, dimensions of two existing ablution units at selected mosques were evaluated using ‘Ablution Unit Dimension Evaluation’ form. Results: New ablution area design was developed based on elderly and disabled people anthropometric dimension and user preferences as well as user satisfaction survey. This study can be considered as preliminary study for the de-velopment of ergonomic ablution unit design. Conclusion: It is hoped that the findings and recommendations from this research will be referred by the stakehold-ers to determine the best solution to increase the level of comfort and accessibility for elderly and disabled at mosques in Malaysia.